Pengurangan Waktu Pengambilan Barang dengan Menggunakan Simulasi pada Gudang Sepeda di UD X - Hendra Soesatyo (Jurnal Titra, 2016)
UD X is a company that work in bicycle selling and distribution. Some of problems that occur in UD X’s warehouse is the long pick-up time. The other problem is inability of the warehouse to do FIFO system because the warehouse is using stacking system. This research is done by making a simulation in the current condition to obtain the pick-up time. The proposal of the layout is done by grouping the goods by throughput-to-storage to get the good’s throughput speed. Proposal alternative also made by the single racking with front end depot system and single aisle with font end depot racking system, and tested by simulation. Single racking with front end depot is the best proposal from the simulation test with pick-up time 22,017 seconds better than the current condition. Investation cost is Rp128.200.000,- and the breakeven is 21,6 years. Investation is considered as not feasible since the cost isn’t match with the savings that occur.